The Impact of IFRS Adoption on Audit Fees: Evidence from Jordan - Khaled E. Abu Risheh; Mo'taz Amin Al-Saeed (Journal of Accounting and Management Information Systems (JAMIS), 2014)
This study aims to provide evidence of the impact of International Financial Reporting Standards (IFRS) adoption on audit fees in Jordan. Our study is based on publicly available information obtained from a sample of annual reports from Jordanian industrial companies listed in Amman Stock Exchange (ASE). The final sample consists of data from a total of 1274 financial statements representing 91 listed companies during the period 1998 to 2011. Based on various previous studies; we develop an Ordinary least Squares (OLS) cross-sectional regression has indicated several variables that explain the level of audit fees: client size, operational complexity and various aspects of risks. Furthermore; we develop a new variable which is the goodwill. The results indicate that the adoption of IFRS has significantly increased audit fees for Jordanian listed industrial companies in the IFRS-compliant period. Also, we find that the significantly positive coefficients on Intelligent and Expert Business (INTEXP) suggest that members of international accounting firms charge a higher level of audit fees than local Jordanian CPA firms. On the other hand, the significantly positive coefficients on ADOPT*INTEXP suggest that, in the initial years of IFRS adoption, international member firms charge higher incremental audit fees than local Jordanian CPA firms. Furthermore, we find that all control variables (goodwill, accounts receivable, and inventory, loss, firm size and total assets) have significant impact on audit fees. It is our understanding that the impacts of IFRS adoption on audit fees in Jordan have not been widely studied, and we empirically demonstrate that IFRS-related auditing expertise is an important determinant of the audit fees. We recommend that the local Jordanian audit firms should capture potential advantage of being affiliated with international audit firms
Keywords: M41; 650; IFRS; audit fees; goodwill; Amman Stock Exchange; Jordanian Industrial Companies